Habitat associations of rainbow trout Oncorhynchus mykiss and brown trout Salmo trutta fry. Issue 1 (20th October 2021) - Fetherman, Eric R.; Avila, Brian W.
Abstract: Habitat restoration activities continue to increase in large rivers, but many of these projects focus on improving juvenile or adult habitats. Incorporating the habitat associations of fry into restoration designs will allow for broader successes from restoration for all life stages and may be useful for either multispecies or specific‐species management. This study investigated the habitat associations of rainbow trout Oncorhynchus mykiss and brown trout Salmo trutta fry in the upper Colorado River, focusing on the mean substrate size ( D 50 ), velocity (m s −1 ), depth (m) and presence of wood in near‐shore habitats. S. trutta and O. mykiss were found in higher numbers in fry sites with a D 50 of 151 mm (ranging from 96 to 206 mm), velocities ranging from 0.20 to 0.23 m s −1 and depths ranging from 0.17 to 0.18 m. Although there was considerable overlap in habitat associations between the two species, there may be opportunities for single‐species management, if this is a goal of such restoration activities, by adjusting design criteria based on differing habitat associations. In addition, the results suggest that including larger particle sizes in near‐shore habitats and upstream of fry sites could decrease Tubifex tubifex habitat and thereby fry infection severity by reducing exposure to Myxobolus cerebralis . Stocking, interspecific competition and/or the presence of pathogens can affect fry habitat associations and cause deviations from demonstrated suitability indices. As such, evaluating system‐specific differences in habitat associations may allow future habitat restoration activities to be more effective.